Hospitals, health and death in Gaza - Marcos Arana-Cedeño (Social Medicine Publication Group, 2023)
Human rights violations harm dignity and inflict suffering by causing loss of health and/or life.  Thus, illness and death are the most tangible and irrefutable evidence of the commission of these crimes.  The mounting death and injury toll from Israel's siege of Gaza, as well as its relentness and indiscriminate shelling against civilian population is part of a cruel and unjustified collective punishment of Palestinians. Any honest health worker could use the figures of civilian deaths and injuries caused by the Israeli army every day, to count on enough arguments to refute the lukewarmness and ambiguity with which the spokespersons of several country governments and international organizations hesitate to demand a ceasefire and to denounce this massacre as a crime against humanity or  a genocide.